2020
DOI: 10.1096/fj.202001183r
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 2 regulates skeletal muscle development through ribosomal protein S6 kinase 1

Abstract: HMGB2, a DNA‐binding protein, highly expresses during embryogenesis and plays an important role in development of some organs and tissues. However, it remains to be further investigated weather HMGB2 influences muscle development. In this work, we identified HMGB2 as an essential factor in myogenesis. Compared to wild type (WT) mice, body weights of systemic hmgb2 homozygous knockout (hmgb2−/−) mice especially males were reduced. Diameter and cross‐section area of tibialis anterior (TA) muscle fibers as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…14,44 Maintaining HMGB2 expression is required for the proliferation of mouse hepatocyte cells 12 and is critical for satellite cell proliferation and muscle regeneration. 45 These results suggest that HMGB2 is essential for cell proliferation. The pathogenesis of PH involves an imbalance between cell proliferation and death, which occurs with inflammation and shares several features analogous to carcinogenesis 20 ; therefore, investigating the role of HMGB2 in PH is of significant interest.…”
Section: Discussionmentioning
confidence: 91%
“…14,44 Maintaining HMGB2 expression is required for the proliferation of mouse hepatocyte cells 12 and is critical for satellite cell proliferation and muscle regeneration. 45 These results suggest that HMGB2 is essential for cell proliferation. The pathogenesis of PH involves an imbalance between cell proliferation and death, which occurs with inflammation and shares several features analogous to carcinogenesis 20 ; therefore, investigating the role of HMGB2 in PH is of significant interest.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, increased DCN expression in pectoral muscle during the late embryonic stage is associated with muscle weakness in low-score-normal (LSN) individuals [ 31 , 32 ]. Posttranslational modifications mediated by 90 kDa ribosomal protein S6 kinase (RPS6KA1) are necessary for muscle differentiation and hypertrophy [ 33 , 34 ]. S6K deficiency may lead to reduced protein synthesis and specifically trigger muscle cell atrophy in skeletal muscle cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of HMGB2 expression at a basal level is essential for satellite cell proliferation and muscle regeneration [191]. It has been shown that HMGB2 interacts with ribosomal protein kinase S6 beta-1 (S6K1) and regulates its activity during cell proliferation.…”
Section: Decreased Hmgb2 Expressionmentioning
confidence: 99%